Analisis Potensi Longsor Berdasarkan Amplifikasi Kendaraan Di Jalan Trans Sulawesi Kecamatan Tomilito - Meilan Demulawa (Peneliti.net, 2023)
This scientific work aims to determine the value of vehicle amplification. Data processing uses Geopsy software with HVSR analysis, and the analysis results produce amplification values. From the results of the discussion, it can be concluded that for areas where landslides have not occurred, locations I, II, and V. Location I with low soil classification, the amplification value of each truck vehicle is 2.52, car 2.63, and motorcycle 2.26. In location II, where landslides have not yet occurred, the medium soil classification is for trucks with an amplification value of 3.47. In contrast, the low classification for cars and motorcycles has an amplification value of 2.73 and 2.77, respectively. For location V, which is far from the main road, the amplification value of 4.26 is included in the medium soil classification. Meanwhile, landslides have occurred in locations III, IV, and VI. Locations III, IV, and VI are where landslides have occurred with moderate and high soil classifications. Location III is included in the moderate classification with an amplification value of 4.08 for trucks, 4.37 for cars and 4.38 for motorbikes. Location IV, the amplification value of each vehicle (6.47 (truck), 6.08 (car)) is included in the high classification, while the amplification value of motorbike vehicles is 5.73 in the medium classification. Location VI is far from the main road, and landslides have occurred with an amplification value 6.20 with high soil classification